The Importance of Introducing Local Culture to Develop the Character of Early Childhood - Made Ayu Anggreni; Jahju Hartanti; Adi Winarno (PT. Anagata Sembagi Education, 2025)
The introduction of local culture in Early Childhood Education (ECE) is regarded as a strategic approach to fostering character development from an early age. This article outlines both theoretical foundations and recent empirical evidence regarding the role of local cultural elements such as indigenous values, regional languages, folktales, rituals, and community practices in shaping children’s core character traits, including religiosity, honesty, responsibility, discipline, empathy, cooperation, and patriotism. Through a narrative literature review and thematic synthesis of more than 40 scholarly sources, this study develops the “4L-CARE” conceptual model (Language, Lore, Local Practices, Landscape → Character, Agency, Relatedness, Empathy) that explains the linkage between local cultural experiences and character competencies in children aged 4–6 years. Furthermore, the article proposes practical strategies for implementing the Merdeka Curriculum within culturally contextual PAUD settings, including storytelling-based (masatua/folklore) activities, character assessment rubrics, and models of collaboration among teachers, parents, and local communities. The findings emphasize that authentic, repetitive, and meaningful integration of local culture supported by a safe and inclusive local language environment enhances the internalization of character values through play, storytelling, and community-based projects.